Pengembangan Instrumen Penilaian Portofolio dalam Pembelajaran Bahasa Indonesia - Sawalichia Kusuma Ningrum (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Assessment is very necessary in evaluating student performance. Portfolio assessment is useful for measuring students' ability to formulate and reflect on an assignment by collecting material related to predetermined goals and desires. This research aims to identify, explain and summarize. Forms of developing portfolio assessment instruments in Indonesian language learning. The research method used is the literature review research method. The research results show that in portfolio assessment, the implications of portfolio assessment that refer to criteria can influence students, teachers and parents.